Evaluating an Open University Web Course: Issues and innovations - Weller, Martin; Mason, Robin (Proceedings of the International Conference on Networked Learning, 2000)
In 1999 the UK Open University (UKOU) piloted an innovative web based entry level course which provide.cl an introduction to the Internet and computers. The course represents the UKOU's first large scale offering which is solely web base.cl, with online tuition. The course was piloted with 850 students, and extensive evaluation was undertaken. This paper identifies six main issues which affected student's satisfaction and performance on the course: the skills taught in the course; the level of starting knowledge; the use of computer conferencing; participation in online group activities; online tutor support; and time associated with studying. In general the course was successful and student satisfaction was high amongst those who complete.cl it. In 2000 the course is being presented to over 12,000 students.